BIOSTRATIGRAPHIC ZONATION OF THE UPPER CRETACEOUS IN THE EAST EUROPEAN PLATFORM - Olfer'ev A.G.; Alekseev A.S. (My University, 2003)
Two biostratigraphic zonations, one based on macrofauna (primarily on inocerams and belemnites) and the other one based on microfossils, mostly on benthic foraminifers, are distinguished in the regional scale of the Upper Cretaceous of the East European platform. Both zonations are correlated to each other and with the Global Upper Cretaceous Scale (Olfer'ev and Alekseev, 2002).
Keywords: Upper Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая